Fast Fourier transform scanning spreading resistance microscopy: a novel technique to overcome the limitations of classical conductive AFM techniques. (6th August 2015) - Eyben, P; Bisiaux, P; Schulze, A; Nazir, A; Vandervorst, W
Abstract: A new atomic force microscopy (AFM)-based technique named fast Fourier transform scanning spreading-resistance microscopy (FFT-SSRM) has been developed. FFT-SSRM offers the ability to isolate the local spreading resistance (Sr) from the parasitic series resistance (probe, bulk, and back contact). The parasitic series resistance limits the use of classical SSRM in confined volumes and on very highly doped materials, two increasingly important situations in nanoelectronic components. This is realized via a force modulation at controlled frequency (affecting the SR component) and the extraction of the resistance amplitude at the modulation frequency, performing an FFT-based lock-in deconvolution. A systematic evaluation of the FFT-SSRM performances (i.e., resolution, dynamic range, sensitivity, and repeatability) is presented. The impact of various parameters (i.e., modulation frequency and amplitude or cutoff frequency of the current amplifier) on the performances of FFT-SSRM has been evaluated. We demonstrate the possibility to overcome sensitivity losses due to tip saturation in highly doped material and the utility of the technique in two different structures, presenting isolated and confined volumes.